Evaluation of the Early Indicators, Including Arthralgia, in Diagnosing Brucellosis Arthritis - Qian Li; Shupeng Song; Shuanghe Xu; Lisheng Jiang; Yinghua Lan; Yongguo Li (International Journal of Clinical Practice)
Conclusions: NRS showed potential in identifying subclinical presentations of arthropathic manifestations related to brucellosis in this cohort. This result indicates the need for further validation as a potential screening tool for early-stage articular complications.